PENGARUH KEPUASAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Guru SMK Negeri 2 Purworejo) - Heri Kurniadi (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2017)
This research aims to know: 1) The influence of job satisfaction toward the teachers’ motivations in SMK Negeri 2 Purworejo, 2) The influence of job discipline toward the teachers’ motivation in SMK Negeri 2 Purworejo, 3) The influence of job satisfaction toward the teachers’ performance in SMK Negeri 2 Purworejo, 4) The influence of job discipline toward the teachers’ performance in SMK Negeri 2 Purworejo, 5) The influence of motivation toward the teachers’ performance in SMK Negeri 2 Purworejo The data are collected from 60 respondens by using random sampling method. They are analyzed through the research instruments such as a product moment test and the reliability test by using a Cronbach Alpha tecnique; hypothesis test uses a path regression analysis. The research result shows that: 1) there is an influence of job satisfaction toward the teachers’ motivation in SMK Negeri 2 Purworejo (hypothesis proved) , 2) there is an influence of job discipline toward the teachers’ motivation in SMK Negeri 2 Purworejo (hypothesis proved), 3) there is an influence of job satisfaction toward the teachers’ performance in SMK Negeri 2 Purworejo (hypothesis proved), 4) there is an influence of job discipline toward the teachers’ performance in SMK Negeri 2 Purworejo (hypothesis proved), 5) there is an influence of motivation toward the teachers’ performance in SMK Negeri 2 Purworejo (hypothesis proved). The path regression analysis shows that: 1) motivation is proved as intervening variable, but direct effect is the influence job satisfaction toward the performance more dominant than indirect effect is the influence job satisfaction toward the performance pass through motivation, 2) motivation is proved as intervening variable, but direct effect is the influence job discipline toward the performance more dominant than indirect effect is the influence job discipline toward the performance pass through motivation. Keywords: job satisfaction, job discipline, motivation, performance